In vitro enzyme inhibitory and cytotoxic studies with Evolvulus alsinoides (Linn.) Linn. Leaf extract: a plant from Ayurveda recognized as Dasapushpam for the management of Alzheimer’s disease and diabetes mellitus - Mettupalayam Kaliyannan Sundaramoorthy, Pavithra (BMC Complement Med Ther, 2020)
BACKGROUND: Evolvulus alsinoides (Linn.) Linn. (Convolvulaceae) is a therapeutic herb alleviating brain patterns associated with three categories of regulatory principles of the body, mind, and behaviour. In the current research, enzyme inhibition and cytotoxic potentials of E. alsinoides (L.) L. leaf extract has been studied validating its potential application. METHODS: The plant phenolics in the leaf extracts obtained via cold-maceration with solvents viz.: n-hexane, chloroform, ethyl acetate, methanol, and water were quantitatively analyzed. The antioxidant potency was evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and Ferric Reducing Ability of Plasma (FRAP) assays at five concentrations (100–500 μg). The enzyme inhibition potential was performed with α-amylase, α-glucosidase, and acetylcholinesterase at seven concentrations (25–500 μg). The experiments were done in triplicates and statistically validated using Minitab-17 and SPSS 22. RESULTS: Water extract contain 45.08 ± 0.02 mg GAE/g, 49.30 ± 0.07 mg GAE/g, 211.21 ± 0.02 mg QE/g tannins, phenolics, flavonoids respectively. Its antioxidant activity was supported by IC(50) 52.43 ± 0.2 μg/mL (DPPH assay) and 41.58 ± 0.03 (FRAP assay). Methanolic extract inhibits α-amylase with IC(50) 1.33 ± 0.05 μg/mL. Water extract inhibits α-glucosidase and acetylcholinesterase with IC(50) 3.58 ± 0.02 μg/mL and 4.46 ± 0.03 μg/mL. Cytotoxicity studies with SH-SY5Y cell-line substantiate the inhibition potential of water extract with IC(50) 103.0035 μg/mL. DISCUSSION AND CONCLUSIONS: The extracts with potent antioxidant and enzyme-inhibiting activity were determined. The findings of the research are the first report about the inhibition effects of Evolvulus alsinoides (Linn.) Linn extracts against α-amylase, α-glucosidase and acetylcholinesterase. The extracts shall be examined in future studies to evaluate its pharmaceutical potential.